Children as co‐researchers in pandemic times: Power and participation in the use of digital dialogues with children during the COVID‐19 lockdown - Donegan, Aoife; Devine, Dympna; Martinez‐Sainz, Gabriela; Symonds, Jennifer; Sloan, Seaneen (Children & society, 2023)
This paper documents co‐participatory research with children in six primary schools in Ireland during the COVID‐19 pandemic. It explores the use of what we term digital dialogues with diverse groups of children aged 9–10 years as members of Child Research Advisory Groups. The paper conceptualises the digital dialogues as sites of resistance as well as constraint, empowering children to articulate their voices in relation to schooling and the pandemic, whilst mediated by power dynamics—between adults and children, and between children, in the articulation of those voices.